Fish's clinical psychopathology : signs and symptoms in psychiatry - Casey, Patricia R.; Fish, F. J. (Frank James). (Cambridge : Cambridge University Press, 2007)
Fish's Clinical Psychopathology has shaped the psychiatric training and clinical practice of several generations of psychiatrists, but has been out of print for many years. The third edition of this modern classic presents the clinical descriptions and psychopathological insights of Fish to a new generation of students and practitioners. This is an essential text for students of medicine, trainees in psychiatry and practising psychiatrists. It will also be of interest to psychiatric nurses, mental health social workers, clinical psychologists and all readers who value concise descriptions of the symptoms of mental illness and astute accounts of the many and varied manifestations of disordered psychological function. Completely revised edition of classic text. New sections on personality disorder, cognitive distortion, defence mechanisms, memory and unusual psychiatric syndromes. Updated references to contemporary literature.
Title from publisher's bibliographic system (viewed on 19 Feb 2018).
Keywords: Psychology, Pathological